Rapid Recovery of Visual Acuity after Lumboperitoneal Shunt Operation in Malignant Idiopathic Intracranial Hypertension - Levent Sinan Bir; Eylem Degirmenci; Cagdas Erdogan; Selma Bilgin; Erdal Coşkun (Case Reports in Ophthalmological Medicine)
Background. Idiopathic intracranial hypertension can cause rapid deterioration of visual acuity in some severe cases, and these cases are usually thought to have “malignant” form of this disease. Case. In this paper, we report on a 16-year-old girl who is a typical example for malignant idiopathic intracranial hypertension with a rapid recovery of visual acuity after lumboperitoneal shunt operation. Observations and Conclusions. Malignant form of idiopathic intracranial hypertension must be kept in mind in selected patients to avoid irreversible visual loss.